2004
DOI: 10.1242/dev.01399
|View full text |Cite
|
Sign up to set email alerts
|

Tbx1 regulates fibroblast growth factors in the anterior heart field through a reinforcing autoregulatory loop involving forkhead transcription factors

Abstract: Birth defects, which occur in one out of 20 live births, often affect multiple organs that have common developmental origins. Human and mouse studies indicate that haploinsufficiency of the transcription factor TBX1 disrupts pharyngeal arch development, resulting in the cardiac and craniofacial features associated with microdeletion of 22q11 (del22q11), the most frequent human deletion syndrome. Here, we have generated an allelic series of Tbx1 deficiency that reveals a lower critical threshold for Tbx1 activi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
244
0
2

Year Published

2004
2004
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 235 publications
(257 citation statements)
references
References 40 publications
11
244
0
2
Order By: Relevance
“…Furthermore, we have shown that the Tbx1 requirement is intrinsic to the mesoderm. The loss and hypoplasia of the second and first branchial arch muscles in the Tbx1 mutant mouse may be due to intrinsic defects in the mesoderm or secondary to endodermal defects such as the absence of Fgf8 (Vitelli et al, 2002b;Hu et al, 2004;Kelly et al, 2004;Zhang et al, 2005). The endoderm is known to have a key role in patterning the facial structures signaling to the underlying mesoderm and ectomesenchyme (Couly et al, 2002;Ladher et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, we have shown that the Tbx1 requirement is intrinsic to the mesoderm. The loss and hypoplasia of the second and first branchial arch muscles in the Tbx1 mutant mouse may be due to intrinsic defects in the mesoderm or secondary to endodermal defects such as the absence of Fgf8 (Vitelli et al, 2002b;Hu et al, 2004;Kelly et al, 2004;Zhang et al, 2005). The endoderm is known to have a key role in patterning the facial structures signaling to the underlying mesoderm and ectomesenchyme (Couly et al, 2002;Ladher et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the endodermal signal Fgf8, these include Pax9, Gbx2 in the endoderm, and Fgf10 in the mesoderm (Hu et al, 2004;Ivins et al, 2005). The loss of Fgf10 expression has been proposed to result in the decrease in proliferation in the secondary heart field (Hu et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations